PERSONAL ASSISTANT FOR MEDICATION REMINDER SYSTEM FOR SELF-RELIANT SENIORS CITIZENS - M. Kannan; Raj S, Pradeep; Rajendran M; Varshan T, Shree; Subashchandrabose K (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An automatic alert call system is implemented by the Android application MEDICINE REMINDER. Patient-doctor interactions are highlighted. To relieve patients of the burden of remembering when to provide their medications, alarms can be programmed to remind patients at specific times. It is possible to set alarms for various drugs and times, as well as for the day, time, and description of the medication. The system was developed using an agile software engineering process. NODE-RED process was used to develop the back end, and MIT APP inventor was used to implement the front end. IBM Cloud ant DB will house these particulars. The system prioritizes a user-friendly design and simple navigation. We have worked to create medical reminder systems that are affordable, time-efficient, and promote prescription adherence, even though many of these systems need new technology.